The summer we found the baby - Hest, Amy (Candlewick Press, 2020)
Told from three viewpoints, a brisk historical tale follows the experiences of two sisters who discover an abandoned baby on the library steps, while their estranged friend, racing to complete an important errand for his World War II soldier brother, jumps to the wrong conclusion.